A review of Cryphocricos Signoret, 1850 (Naucoridae: Cryphocricinae) with descriptions of three new species - Sites, Robert W. (Zootaxa, 2021)
The genus Cryphocricos Signoret, 1850 was recently determined in a molecular phylogeny to be distantly related to other taxa of the subfamily Cryphocricinae to the extent that it is now once again the sole member of the subfamily. This exclusively New World group of aquatic bugs lives in fast and usually turbulent current and respires by means of a plastron. Efforts to identify morphological features to distinguish among the species have largely fallen short, and some species have been established based on features that exhibit a high degree of intraspecific variation overlapping those of other species. Presented here is a review of the 13 described species with discussions of their features and photos of type specimens, and three new species from Venezuela and Colombia are described. Also presented is a diagnostic attribute unique to the enigmatic Cryphocricos barozzii Signoret, 1850.